Criticism of the Indonesian Education System in the Novel Namaku Alam by LeilaS. Chudori and its Suitability as a Recommended Literary Book in “Sastra Masuk Kurikulum”: Kritik Sistem Pendidikan Indonesia dalam Novel Namaku Alam karya Leila S. Chudori dan Kelayakannya sebagai Rekomendasi Buku Sastra dalam “Sastra Masuk Kurikulum” - Iva Millatul Azhariyah; U’um Qomariyah (Universitas Negeri Semarang, 2025)
Novels often become social representations that reflect social, political, and economic conditions at a certain time. Education as part of social conditions is also contained in novels as literary works. However, there are still shortcomings in educational practices in Indonesia. This study aims to describe the forms of criticism of the education system in the Novel Namaku Alam by Leila S. Chudori and describe its suitability as a Recommended Literary Book in